On the beat signal synchronisation of interferometric FMCW radars. Issue 8 (1st August 2017) - Tudose, Mihai; Anghel, Andrei; Cacoveanu, Remus; Datcu, Mihai
Abstract : The authors present several beat signal synchronisation methods developed in the framework of interferometric frequency modulated continuous wave (FMCW) radars. Their purpose is to determine by post‐processing the start moment of the beat signal repetition interval. An uncertainty in computing the beginning of the repetition intervals is translated in a phase error, which limits the radar's interferometric capabilities. The performances of the proposed methods are tested on real data acquired with an FMCW radar platform.